Potential impingement factors of information and communication technology usage at rural libraries in Malaysia - Samsuddin, Samsul Farid; Omar, Siti Zobidah; Abu Samah, Bahaman; Bolong, Jusang (Mediterranean Center of Social and Educational Research, 2016)
Rural libraries in Malaysia are purposively built to increase the level of people’s knowledge and thus produce an information society, especially in rural communities. The services and facilities provided are expected to change the lifestyle of the local community. The main objective of this study is to suggest the potential impingement factors for Information and Communication Technology (ICT) usage at rural libraries in Malaysia. This conceptual study is based on document analyses and reviews of previous literature to identify the potential impingement factors for ICT usage in rural libraries. A total of four potential impingement factors are identified and discussed by the authors: demographic, individual, behavioural, and ICT. It is hoped that this study’s results can assist concerned parties in constructing strategies for improving and further cultivating ICT usage among rural communities in Malaysia.